Removal of Nickel(II) from Aqueous Solutions by Adsorption with Modified ZSM- 5 Zeolites - P. Panneerselvam; V. Sathya Selva Bala; N. Thinakaran; P. Baskaralingam; M. Palanichamy; S. Sivanesan (E-Journal of Chemistry)
The sorptive removal of nickel ion from aqueous solutions using modified ZSM-5 zeolites was investigated. Experiments were carried out as a function of solute concentration and different temperatures. Mesoporous material of ZSM-5 zeolite was modified with phosphoric acid by wet method. The modified zeolite was converted to Na+ form using aqueous NaHCO3 solution. The Na+ form of modified zeolite, represented as PNa2--ZSM-5 was characterized by XRD, BET, SEM and AAS techniques. It was then tested for ion exchange with aqueous Ni(SO4) solution. The Ni2+ content of the solution was analyzed by AAS. Phosphoric acid modified PNa2--ZSM-5 zeolite shows higher adsorption capacity than the parent Na-Y zeolite. Equilibrium modeling data were fit to linear Langmuir model then the Freundlich model. These parameter confirmed that sorption of Ni2+ is feasible spontaneous and endothermic.